2009
DOI: 10.1097/qai.0b013e3181b627c2
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Food Insecurity and Mortality Among HIV-Infected Individuals on HAART

Abstract: Background Food insecurity is increasingly recognized as a barrier to optimal treatment outcomes but there is little data on this issue. We assessed associations between food insecurity and mortality in HIV-infected antiretroviral therapy (ART)-treated individuals in Vancouver, British Columbia (BC), and whether body max index (BMI) modified associations. Methods Individuals were recruited from the BC HIV/AIDS drug treatment program in 1998 and 1999, and were followed until June 2007 for outcomes. Food insec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
178
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 200 publications
(184 citation statements)
references
References 50 publications
5
178
1
Order By: Relevance
“…40 This is consistent with studies showing that impacts of food insecurity on HIV-related health outcomes, including immunologic and virologic outcomes, physical health status, and other measures of morbidity, are quite similar in resource-rich and resource-poor countries. 33,34,[39][40][41]59 Such consistency across different settings suggests that food insecurity is a robust and seemingly universal predictor of worse outcomes, which may contribute to the increased need for acute care services.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…40 This is consistent with studies showing that impacts of food insecurity on HIV-related health outcomes, including immunologic and virologic outcomes, physical health status, and other measures of morbidity, are quite similar in resource-rich and resource-poor countries. 33,34,[39][40][41]59 Such consistency across different settings suggests that food insecurity is a robust and seemingly universal predictor of worse outcomes, which may contribute to the increased need for acute care services.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have also shown adverse impacts of food insecurity on morbidity, mortality, and quality of life among HIV-infected individuals. 14,[32][33][34]39,41 Interventions are needed to address food insecurity and its negative impacts on the health and health-care utilization patterns of HIV-infected individuals. Related interventions that address other subsistence needs have shown promise in improving health-care use and treatment outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Food insecurity increases the risk of acquisition of and poor outcomes associated with both infectious and non-communicable diseases [4,5]. In HIV, food insecurity is associated with increased risk of HIV acquisition [6] and transmission [7,8], poor medication adherence [9,10], worse immunologic [10,11] and virologic outcomes [10,12,13], morbidity [14], and mortality [15]. In diabetes, food insecurity is associated with increased risk of type 2 diabetes mellitus (T2DM) [4], poorer diabetes self-management [16,17], poorer glycemic (i.e., blood sugar) control [4], and increased hypoglycemic events [18].…”
Section: Introductionmentioning
confidence: 99%
“…Food insecurity is one of the multiple barriers that individuals face in initiating and adhering to long-term medical therapies such as ART and DOTS, especially in resourcelimited settings [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. Other patient-related barriers include the complexity of the medication regimen [18], emotional distress [7], illness costs to households [19], stigma [20], health beliefs and poverty [4], limited knowledge of the disease [21], difficulty remembering [22], intentional non-adherence due to adverse drug reactions [23] and harmful use of alcohol [24].…”
Section: Introductionmentioning
confidence: 99%